Integrating reflection into a mobile-assisted reading program for learning English as a second language in China - Wang, Fei; Yuizono, Takaya; Wang, Tzu-Yang; Kim, Eunyong; Lu, Yaqin (Frontiers in Education, 2023)
This study is to investigate students’ perception of a mobile-assisted reading program facilitated with reflective activities as well as their preferences for reflection modes adopted. Participants were 60 students from two classes in a Chinese college. Students read passages on mobile applications and completed a reflection in one mode every two weeks. Four modes (paper reflection, e-journal reflection, audio reflection, and collaborative reflection) were adopted in the study. The study lasted approximately nine weeks. At the end of the program, all students were required to complete an anonymous questionnaire concerning their learning perception. In addition, ten students were selected randomly to attend a semi-structured interview. A pretest and a posttest were conducted to observe students’ language gains. Results showed students generally approved of the effect of this mobile-assisted reading and their reading proficiency improved significantly after the program. In addition, most students favored reflective practices as a good way to stimulate interest, deepen understanding and promote reflective and summarizing abilities, but they didn’t consider it a good method to monitor the learning process in the mobile-assisted reading program. As for the preference for reflection mode, most students favored traditional paper reflection and audio reflection, while collaborative reflection and e-journal reflection received the least support. The findings provided implications for educators and app designers.